HUBUNGAN SUMBER INFORMASI, PENGETAHUAN DAN PERAN TENAGA KESEHATAN DENGAN PEMERIKSAAN TRIPLE ELIMINASI - Fitriani Veronika; Dewi Ciselia; Eka Afrika; Siti Aisyah (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
The Triple Elimination Examination (hepatitis, HIV, syphilis) is an effort to eliminate infection with three infectious diseases directly from mother to child, namely HIV/AIDS, Syphilis and Hepatitis B infection which is directly integrated into the maternal and child health program. This type of research was an analytic observational study with a cross sectional design or approach . The population in this study were all pregnant women who came to visit the health center. The sample in this study amounted to 75 respondents. The type of data uses primary data, the dependent variable is the implementation of the Triple Elimination Examination (hepatitis, HIV, syphilis), the independent variable Information Sources, Knowledge. The results of bivariate research on the relationship between sources of information, knowledge and the role of health workers with triple elimination examinations (hepatitis, HIV, syphilis) based on the chi square statistical test, sources of information, p-value 0.022 <0.05, knowledge p-value 0.00 <0.05 and support from health workers p-value 0.000 <0.05, it can be concluded that there is a relationship between sources of information, knowledge and support from health workers with the Implementation of Triple Elimination Examination (hepatitis, HIV, syphilis). As for suggestions to the Koto Baru Health Center, it is hoped that health workers will be more active and prioritize Educational Information Communication (IEC) in providing triple elimination information to pregnant women